1980
DOI: 10.1002/dev.420130307
|View full text |Cite
|
Sign up to set email alerts
|

The effects of social isolation on the behavior of juvenile domestic cats

Abstract: The effects of social isolation on the behavior of juvenile domestic cats were assessed by rearing 4 male and 4 female infant kittens in each of the following rearing conditions: (1) mother-littermate; (2) mother-only; (3) brooder-littermate; and (4) brooder-only. They were then tested twice a week individually and twice a week socially from 2 to 6 1/2 months of age in a playroom, utilizing multiple categories of behavior. The mother-only-reared juveniles were hyperactive in both object play (when tested indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Therefore, based on our results, we cannot conclude that early weaning is the cause of the behaviour changes seen in this study. However, our results are in agreement with previous experimental studies on cats 39 , 40 and other animals 1 , 7 , 12 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, based on our results, we cannot conclude that early weaning is the cause of the behaviour changes seen in this study. However, our results are in agreement with previous experimental studies on cats 39 , 40 and other animals 1 , 7 , 12 .…”
Section: Discussionsupporting
confidence: 94%
“…We discovered that early weaning increased the probability for aggression. In earlier studies conducted on laboratory cats, early weaned cats have showed elevated aggression towards both people and other cats 39 , 40 . However, these cats were separated from their mothers much younger than separation usually occurs in companion cats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, early separation from the queen can result in fear of, or aggressiveness toward, cats and people, learning disabilities, increased activity, and increased predatory behavior. 6,36 Early human handling helps to produce more tame kittens and puppies that are more adaptive to change (stress) throughout their lifetimes. Just a few minutes a day is all that is necessary, although kittens or puppies < 2 weeks old should not be overly handled.…”
Section: Sociality In Dogs and Catsmentioning
confidence: 99%
“…Conspecific bonding in cats and dogs has not been extensively studied, but limited research has demonstrated that puppies have preferred play partners by six months of age [47] and are able to recognise their kin up to two years after separation [48], with social isolation of dogs documented to cause chronic stress [49]. Similarly, distress associated with the separation of littermates has been documented in kittens [50], suggesting that companion animals may form strong social bonds with peers. Indeed, some changes in the behaviour of both dogs and cats following the death of an animal companion have been anecdotally reported by companion animal owners [51].…”
Section: Introductionmentioning
confidence: 99%